From the Desk of Editor in Chief Vol.28(3) 2010 - Islam, Quazi Tarikul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i3.6521 J Bangladesh Coll Phys Surg 2010; 28: 212